Advances in Agrophysical Research - Grundas, Stanislaw; Stepniewski, Andrzej (IntechOpen, 2013)
The idea of this book was born due to the rapid increase of the interest in excellence of agricultural production in the aspect of both - the quality of raw material for food production as well as in the aspect of environment protection. Agrophysics is a field of science that focuses on the quality of agriculture as a whole i.e. the interaction between human and environment, especially the interaction between soil, plant, atmosphere and machine. Physics with its laws, principles and rules is a good tool for description of the interactions, as well as of the results of these interactions. Some aspects of chemistry, biology and other fields of science are also taken under consideration. This interdisciplinary approach can result in holistic description of processes which should lead to improvement of the efficiency of obtaining the raw materials to ensure a sufficient amount of food, safe for human health. This book could be regarded as the contribution to this description. The reader can find some basic as well, as more particular aspects of the contemporary agriculture, starting with the soil characteristics and treatment, plant growth and agricultural products' properties and processing.